1992
DOI: 10.1021/j100194a053
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation kinetics of ventilated waterdrops coated with octadecanol monolayers

Abstract: We have used remote thermometry and video microscopy to monitor simultaneously the temperature and size of evaporating waterdrops coated with monolayers of 1-octadecanol (stearyl alcohol). The experiments are conducted by acoustically levitating individual, 1-3-mm-diameter waterdrops in a 1.5 m/s nitrogen flow conditioned at 0, 35, and 64% relative humidity. We observe a continuous increase in monolayer resistivity as evaporation compresses the monolayer. The change in monolayer resistivity is independent of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…It is also well established from laboratory experiments that the presence of an organic film on a flat liquid surface is able to limit ␣ across the liquid-gas interface. Laboratory studies on synthetic aerosol composed of organic films do suggest that ␣ on the order of 10 Ϫ4 to 10 Ϫ5 are possible (Otani and Wang 1984;Rubel and Gentry 1984;Seaver et al 1992). As noted in McFiggans et al (2006), surfactant films on ambient aerosol are more likely to be expanded and porous, rather than con- …”
Section: ϫ3mentioning
confidence: 99%
“…It is also well established from laboratory experiments that the presence of an organic film on a flat liquid surface is able to limit ␣ across the liquid-gas interface. Laboratory studies on synthetic aerosol composed of organic films do suggest that ␣ on the order of 10 Ϫ4 to 10 Ϫ5 are possible (Otani and Wang 1984;Rubel and Gentry 1984;Seaver et al 1992). As noted in McFiggans et al (2006), surfactant films on ambient aerosol are more likely to be expanded and porous, rather than con- …”
Section: ϫ3mentioning
confidence: 99%
“…Here, we see that depending on droplet size, the sensitivity asymptotes at a value of 1 given sufficiently small α c , with values on the order of 10 −1 to 10 −3 depending on droplet size. In contrast with α T , however, laboratory measurements of α c show that these values can be as low as ∼10 −5 in the presence of organic films on the surface of the droplets [ Rubel and Gentry , 1984; Seaver et al , 1992], and evidence that such particles may exist in the atmosphere has been presented [ Chuang , 2003]. See Barnes [1986] and Chuang [2003] for more comprehensive reviews of this subject.…”
Section: Sensitivity Of the Condensational Growth Ratementioning
confidence: 99%
“…Laboratory experiments have shown that compressed surface films of certain organic compounds can retard evaporation and/or condensation of water from flat surfaces (e.g., Barnes 1986;McNamee et al 1998) and droplets (Snead and Zung 1968;Garrett 1971;Rubel and Gentry 1984;Otani and Wang 1984;Seaver et al 1992;Xiong et al 1998), although the mechanism for such retardation remains unconfirmed. The magnitude of the effect also varies depending on the technique and compounds used.…”
Section: Evidence For Film-forming Compoundsmentioning
confidence: 99%